RANCANG BANGUN DAN UJI KINERJA MESIN SORTASI BUAH DUKU - Warji Warji; Sandi Asmara; Siti Suharyatun (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT The objective of the research was to design and test the sorting machine of 'duku' fruit. The sorting machine was able to sort the fruit into three grades by means of principle of inclined plane and exploiting of mechanical vibration. Machine components consist of frame, hopper, sorting rack, part of output, source of power, transmission and vibrator. Uniformity of the sorting results varied, i.e., grade A equal to 100 %, grade B equal to 50.1 % and grade C equal to 80.1 %. The average level of sorting process was 59.5 % with the working capacity of the machine of 500 kg/ hour. Diterima: 21 Januari 2007, Disetujui: 25 April 2007